2015
DOI: 10.1371/journal.pone.0127381
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Mammary Tumors in Female Dogs Diagnosed during the Period 2002-2012: A Growing Animal Health Problem

Abstract: Epidemiological studies enable us to analyze disease behavior, define risk factors and establish fundamental prognostic criteria, with the purpose of studying different types of diseases. The aim of this study was to determine the epidemiological characteristics of canine mammary tumors diagnosed during the period 2002-2012. The study was based on a retrospective study consisting of 1,917 biopsies of intact dogs that presented mammary gland lesions. Biopsies were sent to the Department of Pathology FMVZ-UNAM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
148
4
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(233 citation statements)
references
References 17 publications
19
148
4
16
Order By: Relevance
“…This is attributed to the high activity of the mammary glands to hormonal stimuli, such as estrogen, in addition to having a greater amount of parenchyma to be stimulated [18]. Our data reinforce that there is a relationship of tumor size with a higher malignancy grade and with a worse prognosis [24].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is attributed to the high activity of the mammary glands to hormonal stimuli, such as estrogen, in addition to having a greater amount of parenchyma to be stimulated [18]. Our data reinforce that there is a relationship of tumor size with a higher malignancy grade and with a worse prognosis [24].…”
Section: Discussionsupporting
confidence: 79%
“…The mean of age was 9.3 years old, whose bitches were not castrated, four of them had at least one gestation and two received an injectable contraceptive. Based on this, it is possible to emphasize that these factors contribute to a greater risk of development of breast tumor in old bitches, not castrated and before or after puberty, as well as the use of contraceptives based on progesterone and estrogen [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some breeds of dogs exhibit increased predilection for development of certain types of cancer (Dobson 2013). As reported by Salas et al (2015), besides poodles and spaniels, German Shepherd females are characterised by an increased risk of occurrence of mammary tumours. Also according to Surdyka and Slaska (2016a, b), German Shepherd-type females constitute more than 30% of various breeds of dogs with diagnosed mammary tumours.…”
Section: Discussionmentioning
confidence: 94%
“…It has been observed that 50% of dogs that have lived up to 10 years die of cancers (Davis and Ostrander 2014). Tumours afflict all dog breeds, with a particularly high incidence in German Shepherd dogs (Jasik and Reichert 2015, Kaldrymidou et al 2015, Salas et al 2015, Treggiari et al 2015, Surdyka and Slaska 2016a. This breed has been found to be susceptible to malignant vascular tumours with angiosarcoma features located in internal organs (Treggiari et al 2015), osteosarcomas (Dobson 2013), skin cancers (Jasik andReichert 2015, Kaldrymidou et al 2015), and mammary cancers (Salas et al 2015, Surdyka andSlaska 2016a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Mammary gland tumours are the most frequent tumours in female dogs as in women, corresponding to 52% of all types of tumours, in which half of those are malignant. [1][2][3] Mammary tumours in both species have similar biological features; thus, canine cancers and cell lines are excellent experimental models for comparative development of new therapies, identification of cancer-associated genes and pathways and understanding of cancer biology and progression. 4 Tumorigenicity and invasiveness are important acquired characteristics for the development and progression of cancers.…”
Section: Introductionmentioning
confidence: 99%